IMPLICATIONS OF AGE WHEN HOMOSEXUAL MALES CHOOSE THEIR PERSONAL TRAINERS (Fiep Bulletin - online, 2015)
The significance associated with the youthful body is intimately related with the values within a model of affective relations which is characteristical in gay culture. During the interviews held among homosexual males between 35 and 45 years of age and who practiced physical activity in gymnasiums located in the south region of Rio de Janeiro, the theme of aging was detected as influential in deciding with personal trainers they choose. They also disclosed to be paroxysmal representatives of hegemonic masculinity and for that praise youthfulness as a necessary qualification that they expect to find in their personal trainers.
Keywords: youth; personal trainer; homosexuality.